Prophylactic Use of Factor VIII: an Economic Evaluation - Bohn, Rhonda L.; Avorn, Jerry; Glynn, Robert J.; Choodnovskiy, Igor; Haschemeyer, Rudy; Aledort, Louis M. (Thrombosis and Haemostasis, 1998)
Background: Since the introduction of exogenous factor VIII therapy, several studies have explored the clinical benefits of prophylactic use of factor VIII. Little research, though, has focused on the economic aspects of this regimen. We conducted a cost analysis using data from the Orthopedic Outcomes Study, a prospective, cross-national study of the clinical outcomes associated with different patterns of factor VIII utilization to examine the health care costs incurred and expenditures averted in patients receiving on-demand versus prophylactic use of factor VIII in hemophilia. Methods and Analysis: 831 patients with severe hemophilia aged 1 to 31 years, from 19 centers around the world were included in the cost analysis. Patients were categorized into three groups according to the number of weeks during the study years in which they received prophylactic regimens of factor VIII. For each subject, we estimated the costs of hospitalization, surgery, days lost from school or work, and factor VIII utilization. Costs were then stratified by age and by joint score to assess confounding, and a multivariate model developed to determine the relationship between use of factor VIII prophylaxis and total costs, while controlling for potential confounders.Results: Patients who received factor VIII episodically incurred substantially greater disability-related costs (days lost from school or work, days hospitalized due to hemophilia, surgery) than patients who received factor VIII prophylactically for some or all of the study period. For all treatment regimens, most disability-related costs were accounted for by hospitalization for hemophilia-related conditions. The cost of factor VIII itself was substantial in all treatment categories but was highest among patients who received year-round prophylaxis, exceeding the savings resulting from reduced disability and other health care expenditures.Conclusions: Reductions in non-factor health care costs and disability associated with prophylactic use of factor VIII in hemophilia were substantial and helped somewhat to offset the much higher costs of this regimen. For certain subgroups, frequent episodic treatment may be more expensive than full-time prophylaxis. However, because of the very high cost of year-round prophylactic use of factor VIII, total health care expenditures were highest among patients receiving this therapeutic regimen. However, because prophylaxis clearly offers important clinical benefits, this approach may be warranted on medical rather than economic grounds.